Association between the Immunophenotype of Peripheral Blood from mCRPC Patients and the Outcomes of Radium-223 Treatment - Elisabet Cantó; Georgia Anguera; Natalia Jiménez; Begoña Mellado; Ona Ramírez; Anais Mariscal; Pablo Maroto; Silvia Vidal (Diagnostics, 2023)
(1) Background: Prostate cancer is the second most common cancer in men, with androgen suppression as the standard treatment. Despite initially responding to castration, most metastatic prostate cancer patients eventually experience progression. In these cases, Radium-223 is the chosen treatment. We hypothesized that the immunophenotype of circulating leukocytes conditions the response to Radium-223 treatment. (2) Material and Methods: In this prospective study, we collected peripheral blood from twelve mCRPC patients and nine healthy donors before (baseline) and during treatment with Radium-223. Immunophenotyping and the percentages of leukocyte–platelet complexes were determined by flow cytometry. The increments or decrements of leukocyte subsets between the baseline and the second Radium-223 injection were also calculated. (3) Results: At baseline, the mCRPC patients had a lower percentages of CD4+ T cells and B cells and higher percentages of NK and neutrophils than the HDs. In addition, they had more OX40+ CD4+ T cells, PD-L1+ CD8low cells, PD-L1+ B cells, PD-L1+ NK cells, and monocyte–platelet complexes than the HDs. Moreover, patients with slow and fast progression had different percentages of PD-L1+ CD8+ T cells. In particular, slow progression patients underwent an increment of PD-L1+ CD8+ T cells after two cycles of Radium-223. (4) Conclusions: The characterization of circulating immune cells before initiating Radium-223 treatment could become a non-invasive indicator of the response.